MANAGING WASTEWATER IN DECENTRALIZED INDONESIA: COULD LOCAL DEMOCRACY IMPROVE PUBLIC SERVICE? - Waskitawati, Diny (Department of Government, FISIP, Universitas Padjadjaran, 2018)
ABSTRACT This article seeks the construal of sounds local democracy and public service improvements in Indonesian decentralization context by bringing the example of wastewater management in Bandung Municipality. Data collected through series of interviews with respected individuals involved in wastewater service, particularly those who directly engage in water and sanitation projects funded by local and external funding sources. Despite the positive view on decentralization could create a more powerful local government in overseeing local development for more effective public service delivery. It also could be tested by the fragile administrative system and the immature local democracy. In the case of wastewater service in Bandung Municipality, for example, the respected institution called PDAM Tirtawening (Bandung Municipality Water Supply Agency) shows less efficient use of fund compared to the same project funded by the AusAID (Australian AID) as one of Indonesian development partners. Sound governance and administrative reform should be employed to achieve better public service performance. Keywords: local democracy, decentralized Indonesia, Bandung Municipality, wastewater management, governance reformgb777